Modelling of membrane bonding response: part 2 finite element simulations of membrane adhesion tests. Issue 3 (23rd February 2022) - Liu, Xueyan; Kasbergen, Cor; Li, Jinlong; Scarpas, Tom; Tzimiris, Georgios
ABSTRACT: The adhesive bonding strength of the membrane layers between the asphalt concrete surface layers and the decks of steel bridges has a strong influence on the fatigue life of orthotropic steel deck bridges (OSDBs). The interfacial properties between the membrane and the layers bonded to it have not been extensively studied in the current orthotropic steel deck bridge system. For the adequate characterisation of the adhesive-bonding strength of various membranes and surrounding materials on OSDBs and for the collection of the necessary parameters for finite element model, details of the membrane adhesion test (MAT) are introduced and simulated by using the adhesive traction-separation interface element which was developed in a companion paper to this contribution (Liu, X., Kasbergen, C., Li, J., & Scarpas, A. (2019). Modelling of membrane bonding response: part 1 development of an adhesive contact interface element. International Journal of Pavement Engineering ). Parametric studies of the adhesive contact element utilised for modelling the membrane bonding layer in the MAT test have been performed on the basis of the combination of different critical strain energy release rates and the characteristic opening length in the constitutive model. Comparison of membrane deformation profiles and the in-time debonding force distribution between experimental observations and finite element simulations have been presented.